PENGARUH FINANCIAL DISTRESS DAN LEVERAGE TERHADAP KONSERVATISME AKUNTANSI PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016 – 2019 - Mishelei Loen, SE., M.Si. (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2021)
Accounting conservatism is a principle of prudence in financial reporting where companies do not rush to recognize and measure assets and profits and immediately recognize losses and debts that may occur. The application of this principle results in a choice of accounting methods intended for methods that report lower earnings or assets and report higher debt. The purpose of this study was to determine the effect of Financial Distress and Leverage on Accounting Conservatism. The population used in this study is the consumer goods industry sector companies listed on the Indonesia Stock Exchange in 2016-2019 which are listed as a registered population of 56 companies, so a sample of 25 companies was obtained. The sampling technique used was purposive sampling technique in which the number of observations obtained in this study was 72. Data analysis was performed using multiple regression models with the help of SPSS version 25 software. From the research results obtained, Financial Distress and Leverage have a simultaneous effect on Accounting Conservatism in Consumer Goods Industry sector Manufacturing Companies listed on the Indonesia Stock Exchange for the 2016-2019 Period. While partially obtained Financial Distress has no significant effect on Accounting Conservatism and Leverage has a significant effect on Accounting Conservatism.